Stock market evidence on the international transmission channels of US monetary policy surprises - Tim Dominik Maurer; Thomas Nitschka (Danmarks Nationalbank, 2021)
This working paper evaluates the economic sources of the stock market responses of 40 countries to surprises in the fed funds rate (FFR), the Fed's forward guidance (FG) and large-scale asset purchases (LSAP). We decompose stock market returns into different components reflecting investors' revisions in expectations (news) about future cash flows, expected returns, real interest rates and the real exchange rate to show that FFR and LSAP surprises affect foreign stock markets because they influence foreign countries' real economic outlook. FG surprises seem to convey non-monetary information, such as the Fed's risk assessment, to which foreign stock markets react.
Keywords: E44; E52; F36; G15; 330; Monetary-policy transmission; international spillovers; news; stock returns; vector autoregression